Ta’lim al-Lughah al-‘Arabiyyah bi Thariqah Mubasyirah li Tarqiyah Maharah al-Kalam - Supriyadi, Moh. (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
When we looked at this method, we realized that it may not be specific to teaching the Arabic language alone, or teaching a specific language, but it is originally methods that were suggested, tried and used in the field of teaching Arabic as a foreign language or a second language, and its use is not uniform in All languages, and then the owners of each language must develop it for their language when they teach it to others, and then we must also when considering this method. The method takes into account the one that the teacher follows in his teaching, and the techniques that the teacher uses in teaching, as well as the specific means in all its forms. The fact is that these measures depend on the teacher, on his personal skill and on the composition of the class.The direct method is very important for the students in learning the Arabic language because it will train their skills in speaking skill or Arabic speaking. This study uses a descriptive research model with case study method which is part of qualitative research, which means that information from different sources or informants is presented in the form of words and language within a particular natural context. Although they find it difficult in the early stages.